Handling Sexual Harassment Complaints in Sri Lanka: Fair Process and Best Practices. (December 2020) - Adikaram, Arosha S.; Kailasapathy, Pavithra
Sexual harassment at the workplace continues to be an issue all over the world. While there are many policies with well laid-out procedures specifying the process to follow when complaints of sexual harassment are received, there is still a lack of knowledge on actual practices of handling sexual harassment complaints and best practices. Data were collected from 35 HR professionals (HRPs) from over 30 companies in Sri Lanka on how sexual harassment complaints were handled. Based on this empirical evidence and literature as well as the theory of organisational justice, a six-stage process that HRPs should follow for a fair, just and effective handling of sexual harassment complaints is proposed. The process comprises of (a) complaint stage, (b) assessment of complaint stage, (c) investigation stage, (d) action stage, (e) appeal stage and (f) post-settlement stage. Best practices of handling sexual harassment complaints identified through the empirical data and literature are also highlighted.